Consumer theory:Some considerations of a behavioural analysis of choice - Foxall, Gordon R. (Cranfield School of Management, 1987)
The dominant paradigm for consumer research in the context of marketing is "cognitive information processing'. The fundamental assumption of this frame of reference is that observable behaviour is necessarily preceded by intrapersonal mental events which also so serve to explain that behaviour. So strongly entrenched is this paradigm that models of consumer choice derived within it readily accommodate critical viewpoints, absorb and assimilate even antithetical models of man such as that presented by radical behaviourism. Behaviourism has been misinterpreted and misrepresented by consumer researchers who have adopted a cognitively-based mode of explanation to the -exclusion of all others. This paper raises the question of how scientific progress is possible in consumer psychology, given the preeminence of this explanatory mode. It argues that cognitive information processing explanations should be subjected deliberately and systematically to a rigorous critique based upon the contrasting assumptions about the causes of behaviour which are found in alternative perspectives. Particular attention is drawn to the potential contribution which radical behaviourism might make in this respect and its role is illustrated through discussion of the explanation of consumer innovativeness.